Latest Insight into the Relation of Metabolic Syndrome with Thyroid Dysfunction (Global Journal of Medical Research, 2015)
The Metabolic syndrome is a modern epidemic and is considrred to be one of the major public health issues of this century. It is constellation of physical conditions and metabolic abnormalities commonly found in association with increased risk for development of Type II diabetes mellitus, cardiovascular disease and other medical conditions. Thyroid hormones play an important role in regulating energy homeostasis. In addition, thyroid hormones can regulate lipoprotein, glucose metabolism and blood pressure. Thus there is possibility of thyroid dysfunction (may be cause or effect) having an association with metabolic syndrome and its component. The study was aimed to find out occurrence of metabolic syndrome in hypothyroid patients and to determine the association between the components of metabolic syndrome and thyroid hypofunction.
Keywords: thyroid; hyperthyroidism; hypothyroidism; subclinical; lipoprotein TRH (thyroid releasing hormone); TSH (thyroid stimulating hormone)